Enhancing efficiency and scientific impact of a clinical trials network: the Pediatric Heart Network Integrated CARdiac Data and Outcomes (iCARD) Collaborative. (6th August 2019) - Pasquali, Sara K.; Kaltman, Jonathan R.; Gaynor, J. William; McCrindle, Brian W.; Newburger, Jane W.; Anderson, Brett R.; Scheurer, Mark A.; Pinto, Nelangi M.; Anderson, Jeffrey B.; Oster, Matthew E.; Jacobs, Jeffrey P.; Marino, Bradley S.; et al.
Abstract: Recent years have seen an exponential increase in the variety of healthcare data captured across numerous sources. However, mechanisms to leverage these data sources to support scientific investigation have remained limited. In 2013 the Pediatric Heart Network (PHN), funded by the National Heart, Lung, and Blood Institute, developed the Integrated CARdiac Data and Outcomes (iCARD) Collaborative with the goals of leveraging available data sources to aid in efficiently planning and conducting PHN studies; supporting integration of PHN data with other sources to foster novel research otherwise not possible; and mentoring young investigators in these areas. This review describes lessons learned through the development of iCARD, initial efforts and scientific output, challenges, and future directions. This information can aid in the use and optimisation of data integration methodologies across other research networks and organisations.